Characterization of Core Microbiomes and Functional Profiles of Mesophilic Anaerobic Digesters Fed With Chlorella vulgaris Green Microalgae and Maize Silage - Wirth, Roland; Böjti, Tamás; Lakatos, Gergely; Maróti, Gergely; Bagi, Zoltán; Rákhely, Gábor; Kovács, Kornél L. (Frontiers in Energy Research, 2019)
Microalgal biomass is an alternative feedstock for biogas production although its C/N ratio is usually lower than optimal, therefore co-fermentation is recommended. Biogas production from photoautotrophically grown Chlorella vulgaris (C. vulgaris) biomass (240 mL CH4 g oTS−1) and co-fermentation with maize silage (330 mL CH4 g oTS−1) has been studied in semi continuous laboratory biogas fermenters. Maize silage control yielded 310 mL CH4 g oTS−1. The microbial community and the read-based functional profiles, derived from these data, were examined during the process by using next-generation metagenome Ion Torrent sequencing technology. The read-based core microbiome consisted of 92 genera from which 60 abundant taxa were directly associated with the microbial methane producing food chain. The data-set was also analyzed in a genome-based approach. Sixty-five bins were assembled, 52 of them belonged in the core biogas producing genera identified by the read-based metagenomes. The read-based and genome-based approaches complemented and verified each other. The functional profiles indicated a variety of glycoside hydrolases. Substantial rearrangements of the methanogen functions have also been observed. Co-fermentation of algal biomass and plant biomass can be carried out for an extended period of time without process failure. The microbial members of the inoculum are well-conserved, feedstock composition changes caused mostly relative abundance alterations in the core microbiome.